THE INFLUENCE OF WORK FATIGUE, WORK STRESS, AND WORKLOAD ON TURNOVER INTENTION IN NON-PNS EMPLOYEES OF THE YOGYAKARTA CITY HEALTH OFFICE - Utami, Nandya Wastha; Prayekti, Prayekti; Purnamarini, Tri Ratna (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Turnover Intention is a mental or psychological choice that exists between an individual's approach to continuing or stopping work. This study aims to examine and analyze the influence of work fatigue, work stress and workload on turnover intention in non-PNS employees of the Yogyakarta City Health Service. The population and sample used in the research were all non-PNS employees of the Yogyakarta City Health Service, totaling 60 people using non-probability sampling techniques, more precisely saturated sampling. This research method is quantitative by collecting data using a questionnaire. Data analysis used SPSS version 25. The results showed that Job Fatigue, Job Stress and Workload had a positive and significant effect on Turnover Intention.